The Development of Science in the Kingdom of Bukhara in the Xvi-Xvii Centuries - Nematjonovich, Nusratov Anvar (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the socio-political and cultural life of the Bukhara khanate in the XVI-XVII centuries, as well as the influence of the representatives of the Shaibani dynasty on the development of pedagogical ideas of the time, are analyzed from a comparative point of view. In particular, in the 16th-17th centuries Bukhara khanate, evidenced opinions about the pedagogical conditions of development in science, art, culture, education and other fields during the rule of the Shaibani dynasty are presented.